Inovatif Music: Kenangan Manis | Musik Inovatif: Kenangan Manis - I Ketut Yudik Setiawan (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
Sweet Memories is a piece of Innovative Music that describes the beautiful moments of the stylist's childhood, which was so special. The work of Sweet Memories is realized by using the media, said Gamelan Semara Pegulingan, Saih Pitu. The problems that will be discussed are how to form and process the creation of the innovative musical works of Sweet Memories. The author's goal is to realize the stylist's childhood idah moments into the work, namely, to remember those special moments so they will never be forgotten. The method that the author applies in the preparation of this work is the Alma M.Hawkins Method which consists of 3 stages including, the Exploration Stage (assessment), the Improvisation Stage (experimental), the Forming Stage